2004
DOI: 10.1002/jbm.b.30128
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of gelatin fibers and gelatin/PCL composite fibrous scaffolds

Abstract: In this article, ultrafine gelatin (Gt) fibers were successfully produced with the use of the electrical spinning or electrospinning technique. A fluorinated alcohol of 2,2,2-trifluoroethanol (TFE) was used as the dissolving solvent. The morphology of the electrospun gelatin fibers was found to be dependent on the alteration of gelatin concentration ranging from 2.5% w/v to 12.5% w/v at 2.5% increment intervals. Based on the electrospun gelatin fibers obtained, 10% w/v gelatin/TFE solution was selected and mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
720
5
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 976 publications
(761 citation statements)
references
References 28 publications
29
720
5
7
Order By: Relevance
“…In our experiments, no additional surface modifications were necessary facilitating cell attachment onto the fibers of the hybrid scaffolds and both electrospun collagen/elastin/PCL and gelatin/PCL supported attachment and proliferation of hASCs. Similar to our results, Zhang et al also reported improved migration when using gelatin/PCL fibrous scaffolds [15]. It is possible that the gradual degradation of PCL in the hybrid scaffold creates more space for cell migration and that gelatin, as a natural protein, provides binding sites for cellular attachment and proliferation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our experiments, no additional surface modifications were necessary facilitating cell attachment onto the fibers of the hybrid scaffolds and both electrospun collagen/elastin/PCL and gelatin/PCL supported attachment and proliferation of hASCs. Similar to our results, Zhang et al also reported improved migration when using gelatin/PCL fibrous scaffolds [15]. It is possible that the gradual degradation of PCL in the hybrid scaffold creates more space for cell migration and that gelatin, as a natural protein, provides binding sites for cellular attachment and proliferation.…”
Section: Discussionsupporting
confidence: 90%
“…In this study the crosslinked electrospun fibrous scaffolds showed a higher tensile strength; however, these scaffolds shrank, and their pore size as well as porosity decreased dramatically during the cross-linking process in glutaraldehyde vapor. Furthermore, a dense layer of fibers hindered cell migration, most likely due to the smaller pore size [15,46,47]. The combination of PCL10% with gelatin10% resulted in significantly higher tensile strength compared to gelatin or collagen and elastin alone and resulted in a uniform and pliant fiber mat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibers fabricated by an electrically driven jet have been employed in various biomedical applications such as tissue engineered constructs and wound healing patches. 16 One of the advantages of ESFs is that a wide variety of macromolecules can be used for fabrication from biologically derived polymers such as gelatin, collagen, silk fibroin, chitosan, and cellulose [17][18][19][20][21] to synthetic polymers such as polyglycolide, poly (L-lactide) (PLLA), poly(e-caprolactone) (PCL), polyurethane, and poly(vinyl alcohol). 22 ESFs made of natural polymers usually possess inferior mechanical properties, while those made of synthetic polymers often lack suitable biological activities.…”
mentioning
confidence: 99%
“…The vascular scaffold should be composed of a durable biomaterial capable of withstanding physiological hemodynamic forces while maintaining structural integrity until mature tissue forms in vivo (6). Electrospinning technology has been widely used for this purpose because this technique permits fabrication of nano-to microscale fibrous matrices and allows for control of the composition, structure, and biomechanical properties of scaffolds (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%